Synthesis of N-Arylcytisine Derivatives Using the Copper-Catalyzed Chan-Lam Coupling - Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (American Chemical Society, 2021)
N-Arylcytisine derivatives are quite rare. We report here a practical methodology to obtain these compounds. Using the copper-catalyzed Chan-Lam coupling, we synthesized newN-arylcytisine derivatives at room temperature, in air and using inexpensive phenylboronic acids. Cytisine and 3,5-dihalocytisines can act as substrates, and among the products, thep-Br-derivative 2r was used as a substrate to obtain biaryl derivatives under Pd-coupling conditions; ester 2j was converted into its acid and amide derivatives using classical carbodiimide conditions. This shows that the Chan-Lam cross-coupling reaction can be included as a versatile synthetic tool in the derivatization of natural products. © 2021 American Chemical Society and American Society of Pharmacognosy